Polyfunctional hydrophilic antioxidants - from molecular design to practical application - N. V. Kandalintseva (Acta Biomedica Scientifica)
The processes of lipid peroxidation are universal phenomena which to a greater or lesser degree always develops in membranous and lipoprotein complexes of living organisms. Arising alongside lipid peroxidation intensification, the oxidative stress is an important pathogenetic factor of wide range of pathoses and pathological disease development, such as widely spread cardiovascular, phlogistic, oncological and endocrine diseases. Natural and synthetic phenolic antioxidants effectively inhibit lipid peroxidation in vitro and in vivo and attract attention of specialists as means of disease and pathosis prevention and treatment connected to oxidative stress development. The majority of biologically active antioxidants have lipophilic properties while their hydrophilic analogues differ favorably by higher velocity of transportation, convenient dosing and injecting which make them irreplaceable for pathosis treatment. The promising character of creation of water-soluble antioxidants, simultaneously possessing antiradical and antiperoxide activities are justified in the review. It is demonstrated that specimens of hydrophilic sulphurous phenolic antioxidants have marked biological activity. Such compounds as S-[3-(hydroxyaryl]propyl]thiosulfates have bioantioxidant, cardioprotective, anti-inflammatory and anti-tumor properties and can be used for correction of pathological conditions associated with the development of oxidative stress. Prospectivity of the further research is determined by the necessity to develop acting medicine components for free-radical pathology therapy.